Effect of spiritual intelligence on leadership effectiveness and food-hygiene practices - Saad, Mazni; See, Toh Poh; Mohamed Adil, Mohamed Azam; Md Kassim, Normalini (AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK, 2018)
This study suggests an effort through a Holistic View of spiritual intelligence to address low-quality food problem at public institutions in East Malaysia. It explored the causal relationship of this value to Food Performance, Leadership Effectiveness, and Food-Hygiene Practice through 210 food handlers. The Partial Least Square Structural Equation Modeling (PLS-SEM) was used to test the relationship. Holistic View was found to have a positively significant relationship with the performance but, not Leadership Effectiveness. Holistic View among food handlers was found unaffected by Food hygiene practices.